Analisis Kepuasan Pasien TNI Sebelum dan Sesudah Penerapan JKN di Ruang Rawat Inap Kelas II RS Dik Pusdikkes Kodiklat TNI AD - Ernawati, Ernawati (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
Patient satisfaction is one of indicator of health care quality measurement and can be used as a benchmark for the hospital. The purpose of this study was to describe the characteristic of TNI patients who are JKN’s based on age, sex, education and rank, determine the performance of member RS DIK PUSDIKKES Kodiklat TNI AD for TNI patients with Servqual method as well as knowing the difference of services before and after impletation of JKN. This is a quantitative study with cross sectional approach using descriptive analysis and cartesian diagram. The study was conducted for 3 months on 100 patients treated at the military class II. The result showed that the level of patient satisfaction based on average dimensions are quite satisfied, but based on the Cartesian diagram there were 13 items that should be prioritized for improvement. The patients are more satisfied with the service before JKN compared to service after JKN. The complicated registration process, service investigations and provision of drugs becomes an important points with the largest gap value. This studies recommended to add modern equipment at RS Dik Pusdikkes Kodiklat RS Army, formed a team of Quality Control to assess service satisfaction on a regular basis.